Comparing instantaneous yield from combine yield monitor against crop cut test estimated yield - Renny Eka Putri,; Yahya, Azmi; Adam, Nor Mariah; Abd Aziz, Samsuzana (2015)
Yield map accuracy is an important element for the successful implementation of precision farming practices. Incorrect yield monitor readings cause errors in the yield maps, which lead to inaccurate management decisions. Two methods, namely instantaneous yield from on-board yield monitoring system mounted on combine harvester and estimated yield from Crop Cutting Test (CCT) method were used in this study to determine the yield variability that exists within a rice plot foe two cropping seasons. The yield monitoring system was designed to measure the instantaneous harvested crop yield during the actual harvesting of the crop with the combine within the individual rice plots. The CCT method was conducted based on a total of 20 sampling points from a 30 m x 18 m sampling grid within the individual plots prior to the harvesting operation with the combine. Analysis was conducted to determine the closeness of fit between instantaneous yield with estimated yield within the test plots. Some similarities could be seen in in the yield variable plots from the yield data obtained from the two determination methods. The Pearson's correlation coefficients between the two yield data were found to be in the range of 0.69 to 0.83. Conclusively, the developed yield monitoring system on-board the rice combine was able to provide measurements with good accuracy not only on the total crop yield of the harvested plot but also the crop yield variability within the plot.